SPE Annual Technical Conference and Exhibition 2012
DOI: 10.2118/154746-ms
|View full text |Cite
|
Sign up to set email alerts
|

Cement Failure Probability under HPHT Conditions Supported by Long Term Lab Studies and Field Cases

Abstract: Cement durability is very important to maintain proper well isolation and stability under HPHT conditions. In the process of well completion and production, pressure decline and temperature variation with time can contribute to cement failure and wellbore stability issues. However, there is no available investigation in the durability and comparison of different types of cement at higher temperature and at different operational scenarios. Three different types of cement (72 pcf, 101 pcf and 118 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Since the mechanical model of casing/cement ring/ formation assembly is axisymmetric, the physical and mechanical model is a plane strain problem in the polar coordinate system (Figure 1). The relevant variables include radial displacement, radial stress, circumferential stress, and shear stress [12][13][14][15][16][17]. Among them, the inner surface of the casing bears the radial stress caused by the increase of wellbore temperature and pressure caused by wellbore fluid.…”
Section: Mechanical Model Of Cement Ringmentioning
confidence: 99%
“…Since the mechanical model of casing/cement ring/ formation assembly is axisymmetric, the physical and mechanical model is a plane strain problem in the polar coordinate system (Figure 1). The relevant variables include radial displacement, radial stress, circumferential stress, and shear stress [12][13][14][15][16][17]. Among them, the inner surface of the casing bears the radial stress caused by the increase of wellbore temperature and pressure caused by wellbore fluid.…”
Section: Mechanical Model Of Cement Ringmentioning
confidence: 99%
“…The integrity of the cement sheath is determined by the intersection of the load‐bearing characteristic curves of each part, avoiding the complicated problem of directly calculating the failure of the first and second interfaces 15 . Heathman found that changes in wellbore pressure can cause the cement sheath to fail 16 . Subsequently, they developed a personalized design method for cement slurry systems to address this issue and applied it to cementing a high‐temperature and high‐pressure gas well in East Texas 17 .…”
Section: Introductionmentioning
confidence: 99%
“…15 Heathman found that changes in wellbore pressure can cause the cement sheath to fail. 16 Subsequently, they developed a personalized design method for cement slurry systems to address this issue and applied it to cementing a hightemperature and high-pressure gas well in East Texas. 17 Z. Shen and Beck developed a 3D finite element model considering five layers of strata to simulate the mechanical response of casing and cement sheath in nonuniform layers with interlayers.…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of an alternative flowmeter, a calibration requires at least two service visits to the site, and the water injection has to be stopped which will affect production. In the actual water injection process, the water injection flowmeter can not be calibrated twice a year that seriously affects the normal water injection metering and the fine water injection development [6][7][8][9]. Therefore, combined with the actual production situation, the paper studies the on-line calibration technology for the field water injection flowmeter that can meet the calibration technical requirements and operation management specifications.…”
Section: Introductionmentioning
confidence: 99%